Socio-scientific themes (un)veiled in Enem: potentialities for the expansion of sources and of textual genres in the teaching and learning process - Fernandes Sobrinho, Marcos (2016)
The context of the investigation is in the editions of the Brazilian National High School Exams (ENEM from 2009 to 2012) which is applied to students who are in the final stage of their basic education in Brazil. It involved 12 state public schools, in six municipalities in the countryside, where 13 Physics teachers participated as volunteers spontaneously. The exam has been guided by the principles of interdisciplinarity and contextualization; both variables are considered the foundation in Science, Technology and Society education (STS), which is presented as a theoretical support, with emphasis to the SSI. The research gathers qualitative and quantitative nuances in which the analytical content perspective and descriptive statistic aspects were selected, respectively for the data analysis. Items in the exam regarding Physics were identified as having potential to promote discussions through socioscientific themes in which the objective was responding to the question: which indicators in the items of Physics in ENEM and in the voice of the subject-teacher can permit to identify, analyze, and systematize possible articulations of discussions of socioscientific themes in teaching? The data demonstrated that the teachers appeal to ENEM items to plan and minister their classes, however in an uncritical way and mainly based on algorithms which are displaced in significance for students. Given that the results seem to falsify the reality of the school context, the alluded difficulty was then disassembled theoretically and empirically. The difficulty was potentially minimized as paths were established in order to allow the teacher to promote discussions through socioscientific themes identified in easily and universally accessible materials (ENEM items).